Comparative prevalence of adenomatous polyps in people aged 45 to 49 years and in people over 50 years of age in a Colombian population: a case-control study - Cano, Diego (2021)
Introduction: Colon and rectal cancer (CRC) is the third most frequent cancer and the fourth cause of cancer death in the world. In Colombia, it is the third leading cause of death from cancer. The most accepted recommendation is to do colonoscopy screening in people 50 to 75 years old. However, recently the American Cancer Association (ACS) has recommended starting screening from the age of 45. In our environment there are no studies on the prevalence of adenomatous polyps in children under 50 years of age. Objective: To compare the prevalence of adenomatous polyps during screening colonoscopy in people aged 45-49 years (cases) and compare it with that of people aged 50 to 75 years (control). Materials and methods: Case-control studies. The data were collected prospectively during the period from January 2018 to November 2019 at the gastroenterology and digestive endoscopy center of Bogotá Colombia. Results: 490 patients were included, 119 cases and 371 controls, case: control ratio was 1: 3. The prevalence of polyps in cases 36.7% and in controls (42.5%) p=0.279. Adenomatous polyps were detected in 18.5% (95% CI 12.4-26.6) of the cases and 32.4% (95% CI 27.7-37.2) of the controls (p=0.004). Conclusion: The prevalence of polyps during screening colonoscopy in people aged 45-49 years is similar to that expected in screening colonoscopies of people between 50-75 years. This finding would favor screening colonoscopy from 45 years of age.